ANALISIS EFEKTIVITAS MEDIATOR DALAM MENANGANI PERKARA PERCERAIAN DI KABUPATEN BOGOR STUDI KASUS DI PENGADILAN AGAMA CIBINONG KELAS 1A - Nisa Dzun Nur’ain; Hambari; Ade Irma Imamah (USRAH: Jurnal Hukum Keluarga Islam, 2026)
Mediation is a mandatory dispute resolution mechanism in civil cases, including divorce cases in Religious Courts, as regulated by Supreme Court Regulation Number 1 of 2016. The high divorce rate in Bogor Regency, particularly at the Cibinong Class IA Religious Court, indicates that marital conflicts are often unresolved by the parties. This study aims to analyze the effectiveness of mediators in handling divorce cases and identify the factors influencing mediation outcomes.This research uses a qualitative approach with a case study method and field research design. Data were collected through in-depth interviews, direct observation, and document analysis. The findings show that mediator effectiveness is influenced by competence, professionalism, communication skills, mediation techniques, and institutional support. However, mediation is often hindered by emotional tensions, prolonged conflicts, and lack of good faith from the parties. Supporting factors include the mediator’s patience, persuasive approach, and shared interests such as children and family continuity. Overall, mediation has not fully achieved optimal effectiveness in resolving divorce disputes. Mediator effectiveness plays a crucial role in determining the success of mediation in divorce cases. Strengthening mediator capacity and encouraging good faith among parties are essential to improve mediation outcomes.